CPA Coaching Course (Book). - Zeff, Stephen A.; Winborne, M. G. (The Accounting Review, 1963)
Reviews the book "CPA Coaching Course," vol. 1 and 2, 2nd ed., by Henry T. Chamberlain and Robert A. Meier.